ANALISIS PEMBELAJARAN PAI PADA SEKOLAH UMUM: (Kajian pada pembelajaran PAI tingkat SMP/MTs) - Hendriyanto Bujangga (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2022)
This article aims to find out how PAI learning is carried out in public schools and the limitations or topics studied both in public schools and madrasas. In this case, the author generally reviews the curriculum, syllabus, and textbooks related to PAI learning and the portion of Islamic religious education in public schools. Based on the results of the study, it is known that there are indeed differences in the application of PAI learning between madrasas and public schools. In public schools, PAI is taught in a limited time, which is only allocated 3 hours of lessons. Especially in Aceh, due to the implementation of qanun on local content, lessons that contain religion in public schools get an additional two hours of lessons. So that previously only 3 hours of lessons have now become 5 hours of lessons, especially in SMP/SMPLB. Although the curriculum contains the same material and objectives, if the portion of PAI learning in public schools is very small, it will certainly have an impact on the output of PAI learning to be achieved in public schools.